Templated folding of the RTX domain of the bacterial toxin adenylate cyclase revealed by single molecule force spectroscopy - Han Wang; Guojun Chen; Hongbin Li (Nature Communications, 2022)
The authors use optical tweezers to show that the folding of repeats-in-toxin (RTX) block-iv in adenylate cyclase is templated by the folded RTX block-v. The findings suggest a possible mechanism for transmitting the folding signal in the RTX domain.